A huntsman’s bite: envenoming from the Malaysian ‘Black & Gold’, Thelcticopis sp. spider (Arachnida: Araneae: Sparassidae: Sparianthinae) - Ahmad Khaldun Ismail; Court DJ; Anthonysamy C (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Most spider species in Malaysia are considered harmless and spider bites are rarely reported. This is partly due to the mild effects from the bite and victims do not seek medical treatment in the hospital. To date, there are few well-documented cases of medically significant bites from indigenous spider species in Malaysia. Here, we report the presentation, clinical management and outcome of two patients following a bite by the yet to be described ‘Black & Gold’ Huntsman spider from the genus Thelcticopis in Malaysia. The first case involved a 42-year-old man who was bitten on the tip of the distal phalanx of his right middle finger and presented with severe pain and local swelling. He was treated symptomatically and was discharged well. The second case involved a 57-year-old woman, who was bitten on the proximal phalanx of her right little finger and presented with severe throbbing pain and progressive swelling. She was treated symptomatically and was discharged after 24 hours observation in the medical ward. However, she noted moderate neck and generalized joints pains especially affecting the hips and knees, one day prior to discharge. She was treated with oral analgesia and symptoms resolved within two days.